Comparing time to recovery in wasting treatment: simplified approach vs. standard protocol among children aged 6–59 months in Ethiopia—a cluster-randomized, controlled, non-inferiority trial - Maru, Yetayesh; Tamiru, Dessalegn; Baye, Kaleab; Chitekwe, Stanley; Kifle, Yehenew G.; Lailou, Arnaud; Belachew, Tefera (Frontiers in Pediatrics, 2024)
Introduction Wasting occurs when the body's nutritional needs are unmet due to insufficient intake or illness. It represents a significant global challenge, with approximately 45 million infants and children under 5 years of age suffering from wasting in 2022. Methods A cluster-randomized, controlled, non-inferiority trial was conducted in three regions of Ethiopia. A non-inferiority margin of 15%, along with a recovery rate of 90% and a minimum acceptable recovery rate of 75%, were considered alongside an intra-cluster correlation coefficient of 0.05 and an anticipated loss to follow-up of 10% in determining the total sample size of 1,052 children. Children with severe acute malnutrition (SAM) in the simplified group received two sachets of ready-to-use therapeutic food (RUTF) daily, while the standard group received RUTF based on their body weight. For moderate acute malnutrition (MAM) cases, the simplified group received one sachet of RUTF, whereas the standard group received one sachet of ready-to-use supplementary food daily. A non-parametric Kaplan–Meir curve was utilized to compare the survival time to recovery. Results A total of 1,032 data points were gathered. For SAM cases, the average length of stay was 8.86 (±3.91) weeks for the simplified protocol and 8.26 (±4.18) weeks for the standard protocol (P = 0.13). For MAM cases, the average length of stay was 8.18 (±2.96) weeks for the simplified approach and 8.32 (±3.55) weeks for the standard protocol (P = 0.61). There was no significant difference (P = 0.502) observed between the simplified protocol [8 weeks, interquartile range (IQR): 7.06–8.94] and the standard protocol [9 weeks (IQR: 8.17–9.83)] among children with SAM on the median time to cure. There was no significant difference (P = 0.502) in the time to cure between the simplified approach [8 weeks (IQR: 7.53–8.47)] and the standard protocol [8 weeks (IQR: 7.66–8.34)] among children with MAM. The survival curves displayed similarity, with the log-rank test not showing significance (P > 0.5), indicating the non-inferiority of the simplified approach for cure time. Conclusion The findings showed that the simplified and standard protocols demonstrated no significant differences in terms of the average duration of stay and time required for recovery. Clinical Trial Registration https://pactr.samrc.ac.za/, Identifier (PACTR202202496481398).